2016
DOI: 10.1007/s12028-016-0280-8
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Chemical DVT Prophylaxis in Severe Traumatic Brain Injury with Invasive Monitoring Devices

Abstract: We conclude that DVT prophylaxis with either LMWH or UH is safe with intracranial pressure monitors in place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Providers should exercise caution when using chemical anticoagulation for the treatment of traumatic DVT in children. Patients with high DVT risk and high bleeding risk present a challenge for providers; the risk of bleeding due to prophylactic doses of enoxaparin is equivocal in adults and unknown in children. Evaluation of prophylaxis regimens including both pharmacologic and nonpharmacologic measures is desperately needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providers should exercise caution when using chemical anticoagulation for the treatment of traumatic DVT in children. Patients with high DVT risk and high bleeding risk present a challenge for providers; the risk of bleeding due to prophylactic doses of enoxaparin is equivocal in adults and unknown in children. Evaluation of prophylaxis regimens including both pharmacologic and nonpharmacologic measures is desperately needed.…”
Section: Discussionmentioning
confidence: 99%
“…27,39,40 Surprisingly, there was no difference in the incidence of PTS, incidence of clot resolution or improvement, incidence of PE (n = 0), or clot propagation (n = 0) between patients treated with anticoagulation and those who were not treated with anticoagulation. In other cohorts of pediatric patients, 28 and high bleeding risk present a challenge for providers; the risk of bleeding due to prophylactic doses of enoxaparin is equivocal in adults 43,44 and unknown in children. Evaluation of prophylaxis regimens including both pharmacologic and nonpharmacologic measures is desperately needed.…”
Section: Discussionmentioning
confidence: 99%
“…14 In this study, the median time to starting DVT prophylaxis was 3.6 days. As opposed to the previous study in patients with TBI, a retrospective study of 46 patients with aneurysmal SAH showed an increased rate of tract hemorrhage and an increased hematoma volume in patients who received subcutaneous unfractionated heparin within 4 hours of EVD placement compared with those who had received it 4-24 hours after EVD placement.…”
Section: Figmentioning
confidence: 64%
“…Although ICPMs are placed to closely evaluate a patient with severe TBI, there appears to be no mortality benefit due to these devices. Retrospective studies by Kostić et al and Shafi et al had a combined total of 2031 patients and both reported no significant improvement in mortality with ICPM use [2,9]. Furthermore, the benchmark evidence from the South American trials: treatment of intracranial pressure, a randomized prospective multicenter study, found that ICP monitoring with a goal < 20 mm Hg to have no benefit in terms of mortality compared to treatment based on clinical examination and imaging [5].…”
Section: Discussionmentioning
confidence: 99%
“…These included (3) ISS and AISspine, (4) ISS and AIS-thorax, (5) ISS and AIS-abdomen, and (6) ISS and AIS-lower extremity. The predictor variables were chosen based on a discussion among coauthors and a review of the literature [8][9][10][11][12][13][14][15][16]. Covariables with statistical significance (p < 0.20) were included in a hierarchical multivariable logistic regression model and the adjusted risk of mortality was reported.…”
Section: Methodsmentioning
confidence: 99%